Plant design for Gresbe Fertilizer Company (Ammonium Sulfate) - Fagela, Estrella B.; Katigbak, Gregorio M.; Ko, Benito C. (Diliman, Quezon City College of Engineering, 1961)
The proposed plant design for a fertilizer plant in the Philippines proposes to produce an annual output of 40,000 metric tons of ammonium sulfate. Costs studies reveals that with a capital investment of P23,000,000.00 and selling the product at P8.50 per bag (of 100 lbs), expect a profit of P6,790,000.00 before taxes and a profit of P2,735,620.00 after taxes annually, expect to recover the capital in eight years and five months.
Plant design.
Typescript
Submitted in partial fulfillment of the requirements in ChE 62 Chemical Engineering Plant Design.
Keywords: Factories -- Design and construction; Chemical plants; Agricultural chemicals industry; Ammonia as fertilizer